SISTEM PEMBERIAN KREDIT CEPAT AMAN (KCA) DI MASA PANDEMI COVID-19 PADA PT PEGADAIAN CABANG MEDAN PETISAH - Sahda, Nabila; Anan, Malesa (Jurnal Manajemen Akuntansi dan Ilmu Ekonomi, 2024)
PT Pegadaian is a non-bank credit institution that provides credit distribution services to the public. The aim of this study is to find out if there are any changes in the system of credit granting during the current COVID-19 pandemic and their influence on the rate of votes in the Pegadaian PT Branch Field of Petisah. As for the data used in this final task, there are primary data and secondary data. Data collection techniques include interviews, observations, and documentation. The data analysis techniques used are qualitative and descriptive. Based on the results of the analysis carried out, it can be concluded that the system of rapid granting of safe credit (KCA) at PT Pegadaian Branch Field Petisah during the pandemic period has undergone changes in accordance with government regulations that restrict mobility and activity in public areas and have an influence on the rate of number of customers in recent years.